Menganalisis Risiko Bisnis dan Mitigasi Risiko Bisnis Pada Budidaya Ikan Lele - Maulana, Arifin; Faisol, Faisol; Anas, Zulviar; Khirdany, Elvin Nury (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
Catfish is a type of fish commodity that is widely cultivated in Indonesia, especially in Sampang district. Based on the results of interviews that researchers conducted with the owner of Sumber Rezeki Catfish Farming, Mr. Moch Yusron S.Pi., the researchers came to conclusions regarding the risk problem in cultivating catfish. Based on this problem, steps have been prepared to overcome the risks in cultivating catfish by business owners. From the discussion above, the author aims to describe the business risks and business risk mitigation that occur in the Sumber Rejeki catfish cultivation business which is located in the Gunung Sekar sub-district, Sampang district, so that from the research objectives that have been set, the researcher will look for more in-depth information using the method. descriptive qualitative research. The data analysis technique used by researchers is an interactive model starting from the stages of data collection, data reduction, data presentation and finally drawing conclusions.  The results of this research are to describe the business risks and mitigate the business risks of Sumber Rezeki Catfish Cultivation MSMEs in Gunung Sekar sub-district, Sampang district.